State-of-the art of endoscopic semeiology of neuroendocrine tumors of the stomach - I. B. Perfil’yev; V. V Delektorskaya; Yu. P. Kuvshinov; B. K. Poddubny; G. V. Ungiadze; S. S. Pirogov; O. A. Malikhova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. The aim of investigation was improve sensitivity and specificity of endoscopic method of investigation in diagnostics of neuroendocrine tumors (NET) of the stomach.Material and methods. The complex endoscopic approach in diagnostics NET of the stomach was developed, that included standard examination, narrow-band imaging (NBI) both as independent study and in combination to optical magnification of the image (x115) and subsequent endoscopic ultrasound investigation (EUS) of the pathological focus. This method had been applied in 53 cases with NET of the stomach in N.N.Blokhin Russian Scientific oncological center of the Russian Academy of Medical Science in a period from 2001 to 2010. Results. Analysis of obtained data has allowed to determine three macroscopic forms of NET – sessile, pedunculated and infiltrative and to reveal characteristic endoscopic and endosonographic criteria at various optional diagnostic approaches.Conclusions. Application of the complex endoscopic approach has allowed to develop endoscopic semeiology of gastric NET. It includes complex of endoscopic and endosonographic signs, characteristic only for this type of neoplasms and provides quite exact differential diagnostics with other forms of epithelial and non-epithelial tumors of the stomach. Besides that, selection of patients for organ-sparing noninvasive radical endoscopic interventions is considerably facilitated.